Body Mass Index (BMI) and Special History on the Event of Gestasional Preeclampsia Study in Jombang District Health Center - Lusianah Meinawati (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The most common cause of maternal death in Indonesia is direct obstetric causes, namely28% bleeding, 24% preeclampsia-eclampsia, 11% infection, while indirect causes are obstetric trauma 5%and others 11%. Preeclampsia is hypertension that arises after 20 weeks of pregnancy accompanied byproteinuria. Preeclampsia ranks second cause of maternal death after bleeding.Purpose: The study aims to analyze body mass index (BMI) and spesific history of the preeclampsiagestasional events.Method: The research was conducted with Cross Sectional research type. The study was conducted inthe working area of Jombang Regency in February dd July 2019. The population in this study were allpregnant women with preeclampsia who conducted examinations in independent practice midwives inFebruary, March 2019 totaling 168 pregnant women. Total sampling technique. The research instrumentused a questionnaire with the value of Cronbach’s Alpha 0.862.Results:The results of the analysis showed that the independent variables associated with the incidence ofpreeclampsia were Body Mass Index with p-value 0.003; Exp (B); 11,234, variable history of hypertensionin pregnancy with p-value 0,000; Exp (B); 11,387, and diabetes variable with p-value 0,003; Exp (B); 11,334.Body mass index in the obesity category, history of hypertension and diabetes are the biggest contributingfactors to the incidence of preeclampsia in pregnancy.Conclusion: The study concluded that history of hypertension and diabetes are the biggest contributingfactors to the incidence of preeclampsia in pregnancy.